Influences of a DRD2 polymorphism on updating of long‐term memory representations and caudate BOLD activity: Magnification in aging. Issue 4 (9th December 2014) - Persson, Jonas; Rieckmann, Anna; Kalpouzos, Grégoria; Fischer, Håkan; Bäckman, Lars
Abstract: A number of genetic polymorphisms are related to individual differences in cognitive performance. Striatal dopamine (DA) functions, associated with cognitive performance, are linked to the TaqIA polymorphism of the DRD2/ANKK1 gene. In humans, presence of an A1 allele of the DRD2/ANKK1‐TaqIA polymorphism is related to reduced density of striatal DA D2 receptors. The resource‐modulation hypothesis assumes that aging‐related losses of neurochemical and structural brain resources modulate the extent to which genetic variations affect cognitive functioning. Here, we tested this hypothesis using functional MRI during long‐term memory (LTM) updating in younger and older carriers and noncarriers of the A1‐allele of the TaqIa polymorphism. We demonstrate that older A1‐carriers have worse memory performance, specifically during LTM updating, compared to noncarriers. Moreover, A1‐carriers exhibited less blood oxygen level‐dependent (BOLD) activation in left caudate nucleus, a region critical to updating. This effect was only seen in older adults, suggesting magnification of genetic effects on functional brain activity in aging. Further, a positive relationship between caudate BOLD activation and updating performance among non‐A1 carriers indicated that caudate activation was behaviorally relevant. These results demonstrate a link between the DRD2/ANKK1‐TaqIA polymorphism and neurocognitive deficits related to LTM updating, and provide novel evidence that this effect is magnified in aging. Hum Brain Mapp 36:1325–1334, 2015 . ©2014 Wiley Periodicals, Inc.